UV-induced synthesis of chitosan-g-polyacrylamide semi-IPN superabsorbent hydrogels - Saber-Samandari, Samaneh; Gazi, Mustafa; Yilmaz, Elvan (Springer, 2012)
Superabsorbent hydrogels of chitosan-g-polyacrylamide with N,N'-methylene-bis-acrylamide as a crosslinker were prepared via UV irradiation in the absence of photoinitiator under homogeneous conditions. The product was characterized by Fourier transform infrared spectroscopy, differential scanning calorimetry, and scanning electron microscopy to confirm the formation of hydrogels. The transparent hydrogels have been observed to exhibit as much as 2987% swelling in acidic solution. In addition, the hydrogel which hydrolyzed for 6 h (0.24 x 10(3) min) can have a water uptake of 106 times its weight (5300% swelling for 0.5 g hydrogel). The effect of several variables such as time, temperature, pH, acrylamide/chitosan ratio, crosslinker amount, and different media was explored. Finally, the prepared hydrogel have been used in adsorption of Zn(II) ions from water with high removal efficiency (0.636 meq g(-1) or 20.8 mg g(-1)) at pH = 7. The experimental data of the adsorption equilibrium from Zn(II) solution fit well with the pseudo-second-order model.
Keywords: Semi-interpenetrating network; UV-induced polymerization; Superabsorbent hydrogel; Chitosan; Acrylamide; Zn(II) ion adsorption